Immunization status and its determinants among children aged 12–23 months at community health centers in Mogadishu, Somalia: a cross-sectional study - Hassan, Shafie Abdulkadir; Abukar, Abdifatah Abdullahi; Gutale, Abdulahi Salad; Hassan, Asma Isak; Haji, Abdulahi Jabril; Nur, Abdulkadir Mohamed; Adam, Mohamed Ibrahim; Hassan, Ahmed Nor Osman; Mohamed, Mowlid Abdikarin; Omar, Abdifetah Ibrahim; Ahmed, Nur Rashid (Frontiers in Pediatrics, 2025)
BackgroundRoutine vaccination is essential in reducing child mortality. This study assessed the determinants of vaccination status and its determinants for children aged 12–23 months in community health centers in Mogadishu, Somalia.MethodsThe study involved 417 mothers, systematically selected from those attending community health centers in Mogadishu for antenatal care between March 25 and June 15, 2024. Data was collected through a structured questionnaire, and SPSS was used for the analysis. Logistic regression analyses of both bivariate and multivariate were conducted to examine the association between dependent and independent variables. The findings were reported as adjusted odds ratios (AOR) with 95% confidence intervals, and a p-value of less than 0.05 determined statistical significance.ResultsVaccination rates showed that 53% of children were fully vaccinated, while 47% had received partial vaccinations. Findings revealed that higher household income was associated with increased odds of partial vaccination status, with families earning $300–$400 monthly being most likely to be partially vaccinated (AOR: 3.247, 95% CI: 1.784–5.910, p = 0.002). Additionally, children whose mothers had no antenatal care (ANC) visits were significantly less likely to be fully vaccinated (AOR = 20.075, 95% CI: 7.385–54.572, p = 0.001) compared to those whose mothers attended four or more ANC visits.ConclusionOur findings revealed that 53% of children were fully vaccinated, with higher household income and regular antenatal care visits associated with increased vaccination rates. Future research should focus on interventions to improve maternal health services and increase access to antenatal care (ANC) to raise vaccination rates in Somalia. Further investigation should explore barriers to vaccination in low-income areas and innovative community engagement strategies.